Prediction of temperature tolerance in Lilium based on distribution and climate data - Jie Xu; Nan Chai; Ting Zhang; Ting Zhu; Yulin Cheng; Shunzhao Sui; Mingyang Li; Daofeng Liu (iScience, 2021)
Summary: There are plenty publications providing guidance for resistant taxa selection by experimental researches while the number of experimental taxa is often restricted. In this study, we presented a concise method to predict the temperature tolerance of wild Lilium in China based on open access botanical and associated environmental datasets. We divided all taxa into five groups to present an overview of Lilium's adaptability to temperature stress. Furthermore, according to the environmental conditions, the prediction of heat and cold tolerance in Lilium was made based on the combined multi-sources data at taxon level. Thirteen taxa with potential temperature tolerance were predicted of 42 taxa. The results showed that not only is tolerance prediction created by large-scale data analysis possible, but that it may supplement traditional laboratory researches with a comprehensive list of taxa.